Mapping the Distribution of Total Suspended Solids (TSS) in Gondang Reservoir, Lamongan Using Multi-Temporal Landsat Imagery - Nurotun Na’imah; Didik Taryana; Puguh Setya Wiyana (Future Space: Studies in Geo-Education, 2024)
Total Suspended Solids (TSS) are defined as particles and materials suspended in water with sizes up to less than 2 µm. High TSS concentrations pose significant hazards by hindering light penetration, disrupting photosynthesis, and reducing oxygen levels in aquatic environments. Conventional TSS monitoring through laboratory tests is often inefficient regarding time, labor, and cost. Consequently, remote sensing technology provides a more efficient alternative for TSS monitoring in reservoirs. This study utilizes Landsat 8 satellite imagery to develop suitable empirical algorithms for estimating TSS concentrations in Gondang Reservoir, Lamongan. It aims to evaluate the spatial distribution of TSS over three years (2016, 2019, and 2022) and analyze changes in TSS conditions throughout these periods. The research employs a quantitative descriptive method, applying the Syarif, Parwati, and Guzman & Santaella algorithms. Results indicate a continuous increase in TSS concentrations annually, with the highest concentrations observed in the reservoir's inlet areas. Accuracy tests reveal a coefficient of determination (R²) of 0.71 for the Syarif algorithm, demonstrating its substantial accuracy in estimating TSS levels in Gondang Reservoir. This study underscores the worsening TSS conditions in the reservoir and highlights the effectiveness of remote sensing technology for environmental monitoring.